Courtiers of Preterite Love: Another Round About the «Donjuanismo» of Álvaro Mesía and Juanito Santa Cruz (BEOIBERÍSTICA - Journal of Iberian, Latin American and Comparative Studies (ISSN: 2560-4163 Online), 2018)
The configuration of Álvaro Mesía and Juanito Santa Cruz according to the archetype of Don Juan is not ideologically neutral or obedient to a gallant topic, but serves Clarín and Galdós to illustrate the pernicious role of the bourgeois state in the context of the Restoration. But the adaptation of the myth to an urban environment modifies it in a radical way: for this reason, the young Santa Cruz ends his novel turned into a shadow run over by the history of Madrid that is being made; while Mesía is, in an almost medieval Vetusta, the only character that is not eventually destroyed.Key words: «donjuanismo», Álvaro Mesía, Juanito Santa Cruz, Pérez Galdós, Clarín.